Change of Meaning behind Meat-specific Words in the History of English - Kowalczyk, Aleksandra (2024)
The aim set to this paper is to discuss English food metaphors named and defined in Kleparski (2008) as cases of foodsemy. Here, we shall be dealing with meaning shifts of meat-related vocabulary items, in which the source domain derives from the riches of the conceptual macrocategory foodstuffs, the target domain being the macrocategory human being. To this end, we shall concentrate on a dozen of figurative extensions of the original senses of lexical items related to the category meat products and many other foodsemic shifts in this area will be employed as backup material or only mentioned in passing in relevant cases. As to the research material, we shall rely on the data derived from various dictionaries, including The Oxford English Dictionary, Green’s Dictionary of Slang, Green’s Dictionary of Slang Online, Random House Historical Dictionary of American Slang, The Diner’s Dictionary and other lexicographic sources. The model of analysis employed in this paper is that of Kleparski (1996, 1997) and further developed in later publications of the author. All in all, the enquiry attempted here is predominantly historical and the method is one of the versions of cognitive linguistics analysis, but there are also elements of sociolinguistics and cultural linguistics.
Keywords: metaphor; metonymy; foodsemic developments; meat products category; the macrocategory human being